Evaluación de la influencia de los fenómenos de difusión sobre los modelos de variación composicional con profundidad (CvsD) en sistemas de hidrocarburos con contenidos inusuales de CO2 disuelto a condiciones iniciales (2021)
The process of characterization and understanding of a basin or reservoir requires the generation of a compositional, robust and representative fluid model that allows generating a characterization of the variation of the PVT properties throughout it. Currently, the Putumayo basin has a fluid model that models the aforementioned properties with a degree of precision of less than 10% but does not consider diffusive effects and their influence on the depth variation model.